Factors Influencing the Frequency and Severity of Depressive Disorder in Parkinson’s Disease Patients (Bangladesh Journal of Neuroscience, 2026)
Background: Parkinson’s disease is the second most common neurodegenerative disease after Alzheimer’s disease. Apart from motor features, Parkinson’s disease has various non-motor symptoms such as neuropsychiatric symptoms, gastrointestinal symptoms, urogenital disturbances, and sleep disorders. Among the neuropsychiatric manifestations depression is the most common but most of the time it remains underdiagnosed and undertreated leading to worsening of symptoms of the disease and deterioration of the quality of life.Objective: This study aimed to determine the factors influencing the frequency and severity of depressive disorder in Parkinson’s disease patients. Methods: This cross-sectional observational comparative study was conducted at the Department of Neurology at BSMMU, Dhaka, for 16 months following ethical approval. A total of 144 Parkinson’s disease patients were enrolled in this study. Following informed written consent from patients, detailed history and thorough clinical examination were carried out along with relevant investigations. Then the frequency and severity of depressive disorders were assessed by the Bangla version Montgomery–Åsberg Depression Rating Scale (MADRS) scale. Data were collected in the semistructured questionnaire and analyzed by SPSS software.Results: A total of 144 patients diagnosed with Parkinson’s disease were enrolled in the study. Among the 144 patients current age range of the majority patients was 51-60 (40.3%) and the minimum age range was >70 (5.6%). The Mean (±SD) age was 56.00 ± 9.94. Among the study patients, 64% were male and 36% were female. 19.4% of patients were normal, 36.1% had mild, 29.9% had moderate and 14.6% had severe levels of depressive disorder. So overall clinically significant depressive disorder (moderate and severe) frequency of this study was 44.5%. Certain variables such as the age of onset, duration of the disease, staging of the disease, on/off fluctuations, end-off-dose wearing off, drug history of Ropinirole, and Entacapone were closely associated with depressive disorder. Among them, Early age of onset (< 50 yrs) (OR 0.380, p-value 0.029), the duration of the disease (Odds ratio 3.429, p-value 0.049), on-off fluctuation (Odds ratio 0.523, p-value 0.047), and staging of the disease (Odds ratio 4.764, p-value 0.000) are independent predictors for depressive disorder.Conclusion: The patients who had Early disease onset (